Application of Shame Culture in Building Teacher Disciplinary Character at MAPN 4 Medan School - Manurung, Okta Elviana; Chaniago, Nasrul Syakur (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This qualitative descriptive study investigates the application of a culture of shame in fostering disciplined character among teachers at MAPN 4 Medan. A culture of shame, rooted in societal norms, emphasizes accountability for misconduct. Data were collected through observation, in-depth interviews, and documentation, involving madrasa principals, vice-principals, teachers, and administrative staff. Analysis followed four stages: data collection, reduction, presentation, and conclusion drawing. The findings indicate that implementing a culture of shame at MAPN 4 Medan has been effective, though not yet fully integrated. Socialization efforts include moral training, motivational programs, and instilling shame-based cultural values. This initiative aims to build teacher discipline and strengthen moral identity, leading to increased responsibility and professionalism. Positive changes observed include a reduction in rule violations and tardiness. While obstacles like cultural resistance exist, the overall approach of cultivating shame alongside motivation has positively impacted disciplined character and moral identity, fostering greater discipline, responsibility, and professionalism, despite the need for individual awareness.